Analysis of the on-water paddling force profile of an elite kayaker - Gomes, B.; Viriato, N.; Sanders, R.; Conceicao, F.; Vilas-Boas, J. P.; Vaz, M. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to develop a system (FPaddle system) to quantify the forces generated on each side of the kayak paddle (left and right), in the blades' plane of maximal force application and in other planes, and to gain more insights about the on-water paddling force profile and associated variables. Using the FPaddle system forces applied on the paddle by an elite female kayaker were measured. Results suggested that the use of strain gages on two different planes provides more detailed information about the forces applied on the paddle throughout the paddling stroke including the exit phase relatively to the used of strain gages only in the plane of maximal force application.